Bio-inspired innovation and national security - Armstrong, Robert E., 1948-2008 (Published for the Center for Technology and National Security Policy by National Defense University Press : [For sale by the Supt. of Docs., U.S. G.P.O.], 2010)
From the Introduction: This volume is designed as an overview of the many applications of biology to the military and national security writ large (with the exception of bioweapons and biomedicine). Policy issues are covered, and original research is presented. The diversity of the authors' backgrounds reflects the breadth of applications and opportunities of biology to modern problems. The read should walk away enlightened as to the many possible ways in which biology is influencing and will continue to influence national security. Authors were asked to provede foresight on trends and indicators in their areas of interest (but not forecasts, which would describe a single future state) in order to better understand their implications for the next 20 years or so.